2012
DOI: 10.1063/1.4703933
|View full text |Cite
|
Sign up to set email alerts
|

Stability of spinmotive force in perpendicularly magnetized nanowires under high magnetic fields

Abstract: Spinmotive force induced by domain wall motion in perpendicularly magnetized nanowires is numerically demonstrated. We show that using nanowires with large magnetic anisotropy can lead to a high stability of spinmotive force under strong magnetic fields. We observe spinmotive force in the order of tens of µV in a multilayered Co/Ni nanowire and in the order of several hundred µV in a L10-ordered FePt nanowire; the latter is two orders of magnitude greater than that in permalloy nanowires reported previously. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Fueled by the verification of the prediction by Barnes and Maekawa, the concept of the SMF has attracted researchers, and there has been some progress in both experiment [75][76][77][78][79] and theory. [107][108][109][110][111][112][113][114][115][116][117][118] In 2011, Yamane et al provided a new formalism of SMF, where the equation of motion of a conduction electron is studied, as will be detailed in the following. If one knows f AE , the induced SMF is calculated in the same way as in the classical electromagnetism, where the inductive electromotive force is induced by f e .…”
Section: Spinmotive Forcementioning
confidence: 99%
“…Fueled by the verification of the prediction by Barnes and Maekawa, the concept of the SMF has attracted researchers, and there has been some progress in both experiment [75][76][77][78][79] and theory. [107][108][109][110][111][112][113][114][115][116][117][118] In 2011, Yamane et al provided a new formalism of SMF, where the equation of motion of a conduction electron is studied, as will be detailed in the following. If one knows f AE , the induced SMF is calculated in the same way as in the classical electromagnetism, where the inductive electromotive force is induced by f e .…”
Section: Spinmotive Forcementioning
confidence: 99%
“…Ferromagnetic nanowires have great potential for ultrahighdensity data storage applications, such as magnetic domainwall racetrack memory and perpendicular magnetic recording, [1][2][3][4][5][6][7][8][9] as well as for spintronic sensors, [10][11][12][13][14][15][16][17] spin torque oscillators, 18,19 excitation of spin waves, 20,21 spinmotive force devices, 22,23 and biomedical applications. 24,25 In magnetic domain-wall racetrack memory, magnetic domains in an array of ferromagnetic nanowires store the data.…”
Section: Introductionmentioning
confidence: 99%
“…We have resolved this difficulty in the NiFe nanowires by considering the materials choice; by using perpendicular magnetic anisotropy (PMA) materials (hard magnets), we have shown that rigid DW motion is achieved, and hence, the associated SMF signals can be stabilized 9) . We have numerically confirmed that SMFs in the order of tens of µV in a multilayered Co/Ni nanowire and in the order of several hundreds of µV in an L10-ordered FePt nanowire with the very large PMA can be obtained.…”
Section: Recent Progressmentioning
confidence: 99%